Analysis of 5 Porter Force in the Contemporary Tourism Development Business "Le Hu Garden" - Purwandini, Komala; Hamdi , Edi; Anindita , Rina; Munandar , Agus (Innovative: Journal Of Social Science Research, 2025)
Indonesia's tourism business grew after the COVID-19 outbreak opened borders. Tourism is essential for some to relieve exhaustion and work stress. This is linked to tourist attractions and foreign and domestic tourism. This potential prompts a nature tourist service provider to examine its competitive edge. This study uses descriptive qualitative research. Interviews, literature reviews, data presentation, and five Porter analysis measures are used. Porter's Five Forces analysis's five factors—substitute competition, threat of entry, industry rivalry, consumer bargaining power, and supplier bargaining power—averaged 1.82. In Porter's Five Forces study, Le Hu Garden's competitive advantage is not threatened by quantitative results from 1.67 to 2.33. This research only examines competitive advantages. Future studies should expand beyond Sumatra and include SWOT and QSPM analyses